2018
DOI: 10.1007/s00401-018-1807-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular anatomy and functions of the choroidal blood-cerebrospinal fluid barrier in health and disease

Abstract: The barrier between the blood and the ventricular cerebrospinal fluid (CSF) is located at the choroid plexuses. At the interface between two circulating fluids, these richly vascularized veil-like structures display a peculiar morphology explained by their developmental origin, and fulfill several functions essential for CNS homeostasis. They form a neuroprotective barrier preventing the accumulation of noxious compounds into the CSF and brain, and secrete CSF, which participates in the maintenance of a stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
261
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(294 citation statements)
references
References 168 publications
(233 reference statements)
8
261
0
4
Order By: Relevance
“…The choroid plexus also constitutively expresses markers of epithelial cells such as ICAM-1 and VCAM-1 [45]. Upon activation, they mediate leukocyte infiltration into the CNS [46]. Here, we found that ICAM-1 and VCAM-1 were markedly increased in the choroid plexus postoperatively, suggesting surgery activates choroidal epithelium.…”
Section: Discussionmentioning
confidence: 52%
“…The choroid plexus also constitutively expresses markers of epithelial cells such as ICAM-1 and VCAM-1 [45]. Upon activation, they mediate leukocyte infiltration into the CNS [46]. Here, we found that ICAM-1 and VCAM-1 were markedly increased in the choroid plexus postoperatively, suggesting surgery activates choroidal epithelium.…”
Section: Discussionmentioning
confidence: 52%
“…Several topics (3,6,11,14,16,23) were differentially weighted across cells from the different brain regions (Fig. S3C), including genes encoding transporters (Fig.…”
Section: Molecular Survey Defines the Cellular Composition Of The Devmentioning
confidence: 99%
“…Built as an epithelial bilayer with an accompanying network of predominantly non-neural cell types and vasculature, the ChP regulates the secretion and composition of CSF that fills the brain's ventricles, bathes stem cells, and reaches neurons via exchange with the interstitial fluid 1 . CSF composition is regulated by de novo synthesis and secretion of signals by epithelial cells, as well as selective transcytosis of blood-borne factors [2][3][4][5] , which regulate neurogenesis 6,7 or guide migration of newborn neurons 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the close proximity to the subventricular zone and to the influence of the CSF in the subgranular zone of the dentate gyrus of the hippocampus (Lun, Monuki, & Lehtinen, 2015;Marques et al, 2017), the CP-CSF system and CP-born molecules have a significant role in adult brain neurogenesis. Moreover, the CP synthesizes and secretes biologically active molecules crucial for brain development, stem cell differentiation, and brain repair (Ghersi-Egea et al, 2018;Planques, Oliveira Moreira, Dubreuil, Prochiantz, & Nardo, 2019). Hence, the CP plays a pivotal role in maintaining brain local microenvironment and CNS homeostasis.…”
mentioning
confidence: 99%